Tingkat Kesehatan Pribadi Siswa Kelas IV Sekolah Dasar di Gugus Yos Sudarso (Indonesian Journal for Physical Education and Sport, 2021)
Yuyun, Fitriani Santoso. 2020. "Personal Hygiene Level of Upper Grade Students (Grade, IV) Elementary School in the Yos Sudarso Cluster, Tulis District of Batang Regency in 2020". Final Project. Physical of Education, Health and Recreation. Faculty of Sport Science. Universitas Negeri Semarang. Supervisor: Dr. Tri Rustiadi, M.Kes.Keywords: Personal Hygiene, Upper Grade, Elementary School Health is very important for humans and therefore they should maintain personal hygiene and instill in children from an early age. Personal hygiene is an effort and action taken by someone to maintain, to preserve and to improve their own health status. The background of this research was because students does not know about personal hygiene therefore, students lack in maintaining cleanliness. This study aims to determine the level of personal hygiene of upper class students (class IV) Elementary School in the Yos Sudarso Cluster, Batang District, 2020. This research is a quantitative descriptive study with a survey method. The operational definition of the research variable is to learn the level of health of 4th grade elementary school students. The research sample is 42 student exams. The research instrument used questionnaires and observations. The sampling technique uses random sampling. The data analysis technique used descriptive analysis with percentage techniques. The results of the study explained that the level of personal hygiene of upper grade (grade IV) elementary schools in the Yos Sudarso Cluster of the Tulis District of Batang Regency in 2020 was for the "highest" category of 11 students or 26.19%. The "higher" category are 25 students or 59.52%. The category of "quite high" as many as 6 students or by 14.29%. The category of "less" is 0 students or 0%. From the results of the research concluded that the level of personal hygiene of upper grade students (grade IV) Elementary School in the Yos Sudarso Cluster Subdistrict Tulis Batang Regency in 2020, included in the high category that is 78.75%. The Suggestions for students should be able to maintain healthy living habits and apply them in everyday life. The Suggestions for teachers should pay more attention to students personal hygiene and provide guidance to students to maintain their health.